Ag+ colorimetric sensor based on graphene oxide/nano-platinum composite - Yanping, Qu; Ibrahim, Yakub; Rubiyah, Baini; WenShuo, Hu; Lizhen, Wang (Springer Nature, 2023)
With the development of society, pollution accidents occur more frequently, and the efects of toxic substances containing silver on human health and environment are increasingly extensive. Therefore, the real-time on-site monitoring of silver ions is urgently needed. Based on the catalase-like properties of graphene/nano-platinum composites and the coupling efect between Pt and Ag+, a simple, unlabeled colorimetric sensing method is proposed to achieve the quantitative detection of Ag+. Under optimal conditions, the detection range of Ag+ by this colorimetric sensing method is 0.5–1000 μM, and the detection limit is 0.5 μM, which is lower than the previously reported detection limit of unlabeled Ag+ colorimetric sensing method, showing higher sensitivity and detection range. Under the same conditions, the sensor has almost no response to interference ions, showing good specifc recognition ability. In addition, the colorimetric sensing method can be used to detect Ag+ in actual water samples, serving as a new paradigm for visual detection of Ag+.